Optimism at Armageddon - Meigs, Mark. author. aut Link
IX, 269 p.
Keywords: An analytical account of the experiences of American soldiers in World War 1 drawing on a wide range of sources in France and the United States. Since American forces did not appear on the Western Front in substantial numbers until the summer of 1918, their experiences of the war were short and less devastating than those of their Allied comrades. Thus surviving American troops emerged from the experience in a rather more upbeat mood about the war than the Allies. This is a fascinating and ground-breaking work as few other military historians have attempted to deal with the US army of 1918 in depth.